Polysaccharide-anchored fatty acid liposome - Tan, H.W.; Misran, M. (2013)
In this study, the preparation of N-pamitoyl chitosan (ChP) anchored oleic acid (OA) liposome was demonstrated. Two different types of water-soluble ChPs with different degrees of acylation (DA) were selected for this study. The presence of ChPs on the surface of OA liposome was confirmed with their micrographs and physicochemical properties. The "peeling off" effect on the surface of the ChP-anchored OA (OAChP) liposomes was observed on the atomic force microscope micrographs and confirmed the presence of the ChPs layer on the liposome surface. The surface tension of the OAChPs liposome solution was found to be higher than that of the OA liposome solution. This result indicated the removal of OA monomer by ChPs from the air-water interface. The increase in the minimum area per headgroup (A min ) of the OA with the presence of ChPs has further proved the interaction between OA monomer and the hydrophobic moieties of the ChPs. The ChPs anchored onto the OA monolayer increased the curvature of the OAChP liposomes monolayer and reduced the liposome size. The size of the OAChP liposomes was reduced by 30 nm as compared with the unmodified OA liposome. Results revealed that the anchored ChPs can improve the integrity and rigidity of the OA liposome.